The new railway line between Köstendorf and Salzburg – Looking back to the past and forward to the future. Issue 6 (8th December 2022) - Seywald, Christian; Rettenbacher, Martin
Abstract: To increase capacity and reduce travel time for long‐distance traffic, the Austrian Federal Railways (ÖBB‐Infrastruktur AG) are planning a new railway line between Köstendorf and Salzburg. The centrepiece of the project is the Flachgau Tunnel – an approx. 16 km long, twin‐tube single‐track tunnel system. The selected tunnel alignment ''K5 optimiert'' was developed in a multi‐year route selection procedure. Further optimisation within the current design stage – the detailed submission – achieved a 200 m shortening in tunnel length. The chosen standard cross‐section was substantiated with life‐cycle‐cost and carbon‐footprint investigations which also coincided with experiences from the construction and operation of existing tunnel structures with varying cross‐sections and travel speeds. Both studies show the advantages of the larger 54 m 2 cross‐section compared to a smaller 44 m 2 cross‐section. Complex hydrogeological conditions require a water pressure‐tight tunnel design capable of withstanding a maximum pressure of approx. 11 bar. These conditions are especially challenging for conventional tunnelling methods and require a waterproofing concept with two independent sealing layers. At present, the construction of the project is scheduled to take place from 2027 until 2040. Abstract: Zur Erhöhung der Kapazität auf der Weststrecke sowie zur Fahrzeitverkürzung im Fernverkehr plant die ÖBB‐Infrastruktur AG eine Neubaustrecke im Abschnitt Köstendorf–Salzburg. Herzstück des Vorhabens ist der etwa 16 km lange Flachgauertunnel, der als eingleisig zweiröhriges Tunnelsystem geplant ist. Die im Zuge des mehrjährigen Trassenauswahlverfahrens entwickelte Auswahltrasse „K5 optimiert" wurde in der laufenden Planungsphase – der vertieften Einreichplanung – adaptiert und damit eine Verkürzung um ca. 200 m Länge erreicht. Erfahrungen aus der Errichtung sowie dem Betrieb von Tunnelbauwerken mit unterschiedlichen lichten Querschnittsflächen und Fahrgeschwindigkeiten wurden in Studien zu Life Cycle Costs sowie zum Carbon Footprint untermauert, in denen Tunnelquerschnitte mit 44 und 54 m 2 gegenübergestellt wurden. Die Ergebnisse beider Studien zeigen die Vorteile des größeren Querschnitts. Komplexe hydrogeologische Rahmenbedingungen erfordern die druckwasserhaltende Ausbildung des gesamten Tunnelbauwerks bei Wasserdrücken von bis zu 11 bar. Bei diesen Rahmenbedingungen wird vor allem bei konventionell aufgefahrenen Abschnitten nahezu Neuland betreten, sodass ein Abdichtungssystem mit zwei voneinander unabhängigen Abdichtungsebenen entworfen wurde. Aus derzeitiger Sicht soll die Neubaustrecke zwischen 2027 und 2040 errichtet werden.